2021
DOI: 10.3390/dairy2010004
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Tract Infections in Dairy Cows: Can Probiotics Curb Down the Incidence Rate?

Abstract: Postpartum uterine diseases are common in dairy cows and are a great concern for the dairy industry as they are associated with various consequences, including lower fertility, lower milk yield, and an overall negative impact on the host health. An infected uterus is a source of bacterial compounds and cytokines that spill into the systemic circulation, spreading inflammation to other organs. In this review article, we discuss a short overview of the anatomy of the reproductive tract of dairy cows and several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 192 publications
(285 reference statements)
1
10
0
1
Order By: Relevance
“…Additionally, more than half respondents perceived that RDs affect dairy cow productivity. The respondents' insight agrees with reports in veterinary literature that report severe economic losses in dairy herds following incidences of RDs, such as slower uterine involution, prolonged interconception and calving interval, reduced reproduction rate, drop in milk production, and increased cost of medication (Abutarbush 2010;Ettinger et al 2017;Radostits et al 2007;Rosales and Ametaj 2021).…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Additionally, more than half respondents perceived that RDs affect dairy cow productivity. The respondents' insight agrees with reports in veterinary literature that report severe economic losses in dairy herds following incidences of RDs, such as slower uterine involution, prolonged interconception and calving interval, reduced reproduction rate, drop in milk production, and increased cost of medication (Abutarbush 2010;Ettinger et al 2017;Radostits et al 2007;Rosales and Ametaj 2021).…”
Section: Discussionsupporting
confidence: 82%
“…Similarly, the majority of respondents reported sharing of calving space with other animals, and a study by Diez and Coelho 2013 showed the importance of this practice for disease transmission between animals. Many RSIs can be shed during calving or at abortion, contaminating the environment and increasing the risk of disease transmission to other animals and humans (Ettinger et al 2017;Hussien 2019;Radostits et al 2007;Rosales and Ametaj 2021).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations